2017
DOI: 10.1021/acsami.7b01547
|View full text |Cite
|
Sign up to set email alerts
|

Study of Electrocatalytic Properties of Metal–Organic Framework PCN-223 for the Oxygen Reduction Reaction

Abstract: A highly robust metal-organic framework (MOF) constructed from Zr oxo clusters and Fe(III) porphyrin linkers, PCN-223-Fe was investigated as a heterogeneous catalyst for oxygen reduction reaction (ORR). Films of the framework were grown on a conductive FTO substrate and showed a high catalytic current upon application of cathodic potentials and achieved high HO/HO selectivity. In addition, the effect of the proton source on the catalytic performance was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(125 citation statements)
references
References 31 publications
4
119
0
1
Order By: Relevance
“…[119] XPS following CPE showed no change in the binding energy of the Fe 2p 3/2 and N1sp eaks. Examination of PCN-223-Fe by ICP-MS before and after the experiment reveals that the iron content in the framework remainsu nchanged, and UV/Vis spectroscopy analysis of the electrolysis solutions howedn oc haracteristic adsorption bands of molecular Fe III TCPP,w hich confirmed that Fe ions did not leach into solution during CPE.…”
Section: Electrocatalytic Mofs For the Orrmentioning
confidence: 85%
“…[119] XPS following CPE showed no change in the binding energy of the Fe 2p 3/2 and N1sp eaks. Examination of PCN-223-Fe by ICP-MS before and after the experiment reveals that the iron content in the framework remainsu nchanged, and UV/Vis spectroscopy analysis of the electrolysis solutions howedn oc haracteristic adsorption bands of molecular Fe III TCPP,w hich confirmed that Fe ions did not leach into solution during CPE.…”
Section: Electrocatalytic Mofs For the Orrmentioning
confidence: 85%
“…In the same year, Usov et al. reported a highly robust MOF named PCN‐223‐Fe by combining Zr 6 oxo clusters and Fe III porphyrin linkers, opening a new route to optimize MOFs as ORR electrocatalysts by selecting proton sources . These results exemplify that it is feasible to use ORR active complexes as the building blocks for preparing ORR‐active MOFs.…”
Section: Classification Of Mof‐based Orr Catalystsmentioning
confidence: 99%
“…Upon adding weak Brönsted acids in the Fe_MOF-525 system, significantly enhanced current densities and better stability were observed. [183] The Zr 4 + ions of PCN-223-Fe with redox inertness play an important role in terms of structural stability and Fe play an essential role in promoting catalytic activity toward ORR. Similar to the study of Hod et al, Usov et al selected the same linkers, Fe(III) porphyrin, to link with Zr 6 oxo clusters, forming a heterogeneous catalyst PCN-223-Fe (Zr 6 O 4 (OH) 4 (Fe(III)-(TCPP) 3 , Figure 16b) with a highly stable structure for the electrocatalytic ORR in 2017.…”
Section: Zr/m Bimetallic-mof Catalystsmentioning
confidence: 99%